An evaluation of the Swedish system of active labour market programmes in the 1990s - Barbara Sianesi (Institute for Fiscal Studies (IFS), 2001)
The low unemployment rates traditionally enjoyed by Sweden have often been attributed to the country's extensive system of active labour market programmes, which have thus frequently been regarded as a model for other countries to emulate. However, unemployment grew enormously in Sweden when the country was hit by a most severe recession in the early 1990s. This paper investigates how effective the Swedish labour market programmes have been in improving the opportunities of unemployed individuals over the last decade. The analyses look at the performance of the Swedish system in its entirety, combining all the programmes into one and focusing in particular on the interactions between the unemployment benefit system and the programme system. In fact, a labour market programme in Sweden effectively comes as a bundle of two conflicting components: it is intended to equip job-seekers with marketable skills which should improve their opportunities on the labour market, but at the same time it allows to renew eligibility to generous unemployment compensation, thus reinforcing the work disincentive associated with the unemployment insurance system. Using extensive information on the labour market history of more than 110,000 individuals followed for five years, the presence of short- and long-term programme effects is investigated in terms of a number of outcomes, including employment and unemployment benefit collection. More specifically, the analyses relate to how unemployed individuals joining a programme per-form, on average, compared to a hypothetical state where they would have waited longer job-searching in open unemployment. Overall, the impact of the programme system is found to have been mixed. Unemployed individuals who go sooner on a programme (compared to later or never), though remaining initially locked-in in the unemployment system for around six months, subsequently enjoy a higher probability of being in employment for up to at least five years. By contrast, the fact that programme participation en Titles individuals to renewed unemployment compensation creates strong incentives to remain within the official unemployment system. Individuals who have joined a programme are thus found to be more likely to return to benefit-compensated un- employment, to re-enter more programmes in the future, or to alternate between benefits and program participation over time than if they had searched longer as openly unemployed. The positive effect on employment does in fact arise because the programmes considerably reduce the chances of being unemployed outside the official unemployment system.
Keywords: C14; J38; J65; J68; 330; Active labour market programs; evaluation; matching; propensity score; treatment effects; unemployment compensation; bounds; missing data; Arbeitsmarktpolitik; Bewertung; Schweden